Clinical Significance of Postoperative Antibiotic Treatment for Positive Islet Cultures After Total Pancreatectomy With Islet Autotransplantation. Issue 7 (11th August 2021) - Naples, Robert; Perlmutter, Breanna C.; Thomas, Jonah D.; McMichael, John; Bottino, Rita; Solomina, Julia; Trucco, Massimo; Augustin, Toms; Simon, Robert; Walsh, R. Matthew
Abstract : Objectives: Islet cultures are routinely performed in total pancreatectomy with islet autotransplantation (TPIAT), and the need for empiric antibiotic treatment based on culture results is unknown. We evaluated the effect of postoperative antibiotic treatment for positive islet cultures on clinical infection. Methods: Seventy-nine patients undergoing TPIAT were reviewed. Prophylactic perioperative ceftriaxone and metronidazole were administered, and transplanted islet preparations included ciprofloxacin. Postoperative antibiotics were not routinely given for positive cultures unless a clinical infection was suspected. The primary end point was 30-day infectious complications. Results: Fifty-one patients (65%) had a positive culture. Overall, 39 patients (87%) had organisms susceptible to our perioperative antibiotic regimen. There was no difference in the infectious complication rate between those with positive compared with negative cultures (16% vs 29%, P = 0.17). Patients with a positive culture had similar 30-day postoperative infectious complication rates whether receiving postoperative antibiotics (n = 7) or not (14% vs 16%, P = 0.91). Only 1 patient had a correlation of clinical and islet cultures. Conclusions: Beyond prophylactic antibiotics, empiric antibiotic treatment for a positive culture is not warranted and provides a rationale for the abandonment of routine cultures in TPIAT.